PENGARUH RASIO LANCAR, PERPUTARAN TOTAL AKTIVA, DAN RASIO UTANG PADA MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Purnasari, Nina; Tarigan, Celly Clara; Feronika, Serli; Sinurat, Romada (Aksara Public, 2019)
This research was conducted to examine the effect of variable Current Ratio, Total Asset Turnover, Debt Ratio on Capital, to Profitability in Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2012-2016. The research sample was 39 manufacturing companies. The data in this study are secondary data and the hypothesis testing method uses multiple linear regression analysis that produces equations Y = -1,085 + 0,249 (Current Ratio) + 0,630 (Total Asset Turn Over) + (-0,308) (Debt to Equity Ratio) + e. The results showed that the current ratio, Total Asset Turnover and debt to equity ratio had a simultaneous influence on profitability, and partially all independent variables (current ratio, Total Asset Turn over and debt to equity ratio) had a significant effect on profitability in the company.